FACTORS INFLUENCING TOURIST SATISFACTION AND REVISIT INTENTION TO CIBUNTU TOURIST VILLAGE DURING COVID-19 PANDEMIC - Rosianna Sianipar; Jimmy M.H. Situmorang; Vasco A.H. Goeltom; Kevin Gustian Yulius (JELAJAH: Journal of Tourism and Hospitality, 2021)
The COVID-19 pandemic has a devastating impact on all world economic activities, including the tourism industry. Tourist satisfaction and revisit intention are two important factors in the recovery of economic activity in the tourism sector. These two variables are also influenced by tourists' perceptions of the COVID-19 protocol implemented by tourist destinations. Desa Wisata Cibuntu puts forward the concept of community-based tourism. Located in Kuningan Regency, West Java, its’ homestay is their main business. This study aims to analyze the factors that influence tourist satisfaction and tourists’ revisit intention to Desa Wisata Cibuntu during the COVID-19 pandemic. This research is an explanatory study that seeks to explain the causative relationships between endogenous and exogenous variables. The sampling technique used in this study was non-probability sampling with a convenience sampling method. The research instrument used was a questionnaire with 25 indicators and the data were analyzed using SEM with 100 respondents. The data obtained from the research instrument shows that all indicators meet the requirements of discriminant validity, convergent validity and reliability. The data were analyzed using the bootstrapping method using 5000 subsamples. The result is the coefficient of determination for tourist satisfaction is 87.6% and for interest in return visits is 91.6%. In the t test, 4 hypotheses were rejected, and 5 hypotheses were accepted. In conclusion, cultural contact has no significant effect on satisfaction and interest in return visits during the COVID-19 pandemic and satisfaction also does not have a significant effect on revisit intention. In this study, the COVID-19 protocol is one of the important factors affecting tourist satisfaction and revisit intention.